Analysis of blood screening strategies and their efficacy among voluntary blood donors in a region of East China - Yiming Jin; Rong Lu; Mingyuan Wang; Zihao Xu; Zhen Liu; Shuhong Xie; Yu Zhang (PLoS ONE, 2025)
Objective In this study, we aimed to analyze the blood screening detection strategies employed for voluntary blood donation in a specific region of East China and evaluate the efficacy of the blood safety detection system. Donors and Methods A total of 539,117 whole blood samples were collected from voluntary blood donors between January 2018 and July 2021, as well as in 2023 and 2024. The samples were screened for hepatitis B surface antigen (HBsAg), hepatitis C virus (HCV) antibodies, human immunodeficiency virus antibodies/antigen (HIV Ab/Ag), and Treponema pallidum (TP) antibodies using enzyme-linked immunosorbent assay (ELISA). Alanine aminotransferase (ALT) levels were measured using a rapid method. Chemiluminescence immunoassay technology was used to detect five hepatitis B virus (HBV) markers. Polymerase chain reaction was employed to detect HBV DNA, HCV RNA, and HIV RNA. The reactivity rates of each marker were analyzed. Results The overall positivity rate for blood testing among donors in this region was 0.76% (4,078/539,117). The positivity rates for the individual markers were as follows: anti-TP (0.20%)> HBsAg (0.18%)> ALT (0.13%)> anti-HCV (0.085%)> nucleic acid testing (0.080%)> HIV antigen/anti-HIV (0.079%). No significant differences were observed (P > 0.05). Before 2023, the positivity rates for ALT and HBsAg exhibited occasional fluctuations, followed by a significant decline. Conversely, in 2024, a slight upward trend in the HIV positivity rate was noted. Conclusion The current multitiered blood screening and detection strategy in this region exhibits complementary advantages, ensuring effective blood safety. However, the observed slight upward trend in the HIV positivity rate among voluntary blood donors highlights the necessity for enhanced pre-donation counseling and risk assessment for key populations.